Sistem Informasi Pendataan Potensi Daerah Di Lingkungan Dinas Tenaga Kerja Provinsi Papua - Hokoyoku, Venezuella Regina Joshina; Lahallo, Jim; Hasan, Patmawati (STMIK Banjarbaru, 2024)
Data collection on regional potential at the Papua Province Manpower Service is currently still manual, so the data collection, processing and dissemination of information is ineffective. This research aims to build an integrated regional potential data collection information system. The waterfall method and object-based analysis are used in system development. The C# programming language is used to build the system. Black box testing is performed to ensure system functionality. The Black box testing that is applied results in testing each system functionality scenario that runs well based on the results of data collection and system design. The regional potential data collection information system has been designed to meet the needs of the Papua Province Manpower Service. This system can help the Manpower Department in managing regional potential data more effectively and efficiently, as well as in producing information that is useful for decision making.Keywords: Information Systems; Regional Potential; Papua ProvinceÂ AbstrakPendataan potensi daerah pada Dinas Tenaga Kerja Provinsi Papua saat ini masih manual, sehingga proses pendataan, pengolahan, dan penyebaran informasi menjadi tidak efektif. Penelitian ini bertujuan untuk membangun sistem informasi pendataan potensi daerah secara terintegrasi. Metode Waterfall dan analisis berbasis objek digunakan dalam pengembangan sistem. Bahasa pemrograman C# digunakan untuk membangun sistem. Pengujian Black box dilakukan untuk memastikan fungsionalitas sistem. Dalam pengujian Black box yang diterapkan menghasilkan pengujian setiap skenario fungsionalitas sistem yang berjalan dengan baik berdasarkan hasil pengumpulan data dan perancangan sistem. Sistem informasi pendataan potensi daerah yang dirancang dapat memenuhi kebutuhan Dinas Tenaga Kerja Provinsi Papua. Sistem ini dapat membantu Dinas Tenaga Kerja dalam mengelola data potensi daerah secara lebih efektif dan efisien, serta dalam menghasilkan informasi yang bermanfaat bagi pengambilan keputusan.Â